Pembingkaian berita krisis Selatan Thailand dalam akhbar aliran perdana di Malaysia - Kasim, Azahar; Mohd Sani, Mohd Azizuddin; Ismail, Awan; Masri, Az Zamakhsyari (Universiti Kebangsaan Malaysia, 2015)
The crises in Southern Thailand involving security issues, terrorism and uncertain directions in three regions has occurred since 1960.In fact, the problem worsened when clashes between residents and troops that caused thousands of Thais killed in 2004.To date, more than 5,700 people killed and over 7,500 injured.Leaders and people in Southern Thailand, majority of Malay ethnic are Muslims, has failed to find the best solution for them and Bangkok based Thai government.Having shared a common border and because of geographical factors, the Malaysian media felt compelled to make news coverage of the crisis in Southern Thailand.Therefore, this study aims to identify the frequency of news broadcasting and to identify news framing construction on the crisis in Southern Thailand in mainstream newspapers in Malaysia.The study was conducted on three newspapers; Harian Metro, Berita Harian and New Straits Times from 1 January 2013 until 31 December 2013. A total of 74 stories that highlighted the crisis in Southern Thailand were published by the three newspapers during the year 2013.From 139 issues, 10 issues classified in this study were displayed.Results showed that crisis news related to attack issues are dominated by Berita Harian while issues related to violence are dominated by Berita Harian and issues related to peace talks are dominated by New Straits Times.